2016
DOI: 10.7863/ultra.15.11049
|View full text |Cite
|
Sign up to set email alerts
|

Management of Clinically and Mammographically Occult Benign Papillary Lesions Diagnosed at Ultrasound‐Guided 14‐Gauge Breast Core Needle Biopsy

Abstract: Uniform surgical excision is not a reasonable management strategy for clinically and mammographically occult benign papillary lesions diagnosed at US-guided 14-gauge breast CNB. Clinically and mammographically occult benign papillary lesions may be subsequently managed by vacuum-assisted removal or imaging follow-up if atypia is not found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Moon et al ., reported that clinically occult benign papillary BLs diagnosed benign at US-guided 14-gauge CNB are not uniformly managed by surgical excision and the short-term follow-up is unnecessary. [2728] Our results also consistent with the results of Rikabi and Husaain who reported 98.2% diagnostic accuracy for tru-cut biopsy (CNB) but he reported the use of 18-gauge needle. [29]…”
Section: Discussionsupporting
confidence: 90%
“…Moon et al ., reported that clinically occult benign papillary BLs diagnosed benign at US-guided 14-gauge CNB are not uniformly managed by surgical excision and the short-term follow-up is unnecessary. [2728] Our results also consistent with the results of Rikabi and Husaain who reported 98.2% diagnostic accuracy for tru-cut biopsy (CNB) but he reported the use of 18-gauge needle. [29]…”
Section: Discussionsupporting
confidence: 90%
“…1.8% BI-RADS 4b-5: 13% resp. 50% No association with age and size lesion Ko et al 2017 [ 63 ] n = 346 PL in CNB Upgrade In VAB ( n = 211) In OE ( n = 135) Upgrade Overall in 2.3% If size < 1cm: 0.9% Size of PL correlates with upgrade Close follow-up with ultrasound instead of excision Moon et al 2016 [ 64 ] n = 65 PL in CNB Upgrade In VAB ( n = 12) In OE ( n = 53) Upgrade In OE in 9% (5/53) In VAB 8% (1/12) No recommendation Niinikoski et al 2018 [ 65 ] n = 80 PL in CNB Small PL in selected patients-OE can be avoided Pareja et al. 2016 [ 66 ] Upgrade in OE ( n = 171) after PL Without atypia In CNB Upgrade In OE 2.3% (4/171) Regardless of size, observation is appropriate at radiologic–pathologic concordant CNB Seely et al 2017 [ 67 ] n = 107 PL in OE Upgrade after VAB ( n = 60) CNB ( n = 47) Upgrade in OE After VAB in 1.6% (1/60) After CNB in 8.5% (4/47) Higher upgrade in OE if PL is diagnosed on CNB Tatarian et al 2016 [ 68 ] n = 16 PL in CNB Upgrade in OE Upgrade in OE In 2/16 cases (12.5%) Surgical excision should be considered in patients with benign papillomas Tran et al 2017 [ 69 ] n = 43 PL in CNB Upgrade in OE Upgrade in OE In 1/43 cases (2%) Low-upgrade rate in OE Wyss et al 2014 [ 70 ] ...…”
Section: Resultsmentioning
confidence: 99%
“…1.8%BI-RADS 4b-5: 13% resp. 50%No association with age and size lesionKo et al 2017 [63] n = 346 PL in CNBUpgradeIn VAB ( n = 211)In OE ( n = 135)UpgradeOverall in 2.3%If size < 1cm: 0.9%Size of PL correlates with upgradeClose follow-up with ultrasound instead of excisionMoon et al 2016 [64] n = 65 PL in CNBUpgradeIn VAB ( n = 12)In OE ( n = 53)UpgradeIn OE in 9% (5/53)In VAB 8% (1/12)No recommendationNiinikoski et al 2018 [65] n = 80 PL in CNBSmall PL in selected patients-OE can be avoidedPareja et al. 2016 [66]Upgrade in OE ( n = 171) after PL Without atypiaIn CNBUpgradeIn OE 2.3% (4/171)Regardless of size, observation is appropriate at radiologic–pathologic concordant CNBSeely et al 2017 [67] n = 107 PL in OEUpgrade afterVAB ( n = 60)CNB ( n = 47)Upgrade in OEAfter VAB in 1.6% (1/60)After CNB in 8.5% (4/47)Higher upgrade in OE if PL is diagnosed on CNBTatarian et al 2016 [68] n = 16 PL in CNBUpgrade in OEUpgrade in OEIn 2/16 cases (12.5%)Surgical excision should be considered in patients with benign papillomasTran et al 2017 [69] n = 43 PL in CNBUpgrade in OEUpgrade in OEIn 1/43 cases (2%)Low-upgrade rate in OEWyss et al 2014 [70] n = 156 PL in CNBUpgradeIn VAB ( n = 135) andFollow-up ( n = 21)(Median 3.5 years)Upgrade after follow-up1.2% (2/156)VAB is recommended as the method of choice for removal of PLYamaguchi et al 2015 [71] n = 142 PLFollow-up imagingAfter VAB ( n = 125)After CNB ( n = 17)Upgrade in OE ( n = 17)4/17Discordant lesions should undergo OEYang et al 2018 [72] n = 116 PL(On CNB or VAB)10 mm or smallerOE n = 74Surveillance n = 42Overall upgrade 11% (13/116)Upgrade after VAB (0%)Upgrade after CNB (16.5%)Higher upgrade in OE-After CNB-Older age-Pl with atypia…”
Section: Resultsmentioning
confidence: 99%
“…Papillary breast lesions represent approximately 4.5% to 10.7% of the breast lesions diagnosed on core needle biopsy (CNB) and vacuum-assisted biopsy. [3][4][5] Their clinical presentations can be either asymptomatic, bloody nipple discharges, or palpable masses depending on the location and size. The radiographic findings include calcifications or solid/cystic mass lesions.…”
Section: Introductionmentioning
confidence: 99%